Polyvinyl butyral intermediate membrane as well as synthesis method and application thereof
By linking the vapor-phase silica nanoparticles with PVB molecules and introducing nano zinc oxide and nano cerium oxide, the problems of PID effect and insufficient light transmittance of PVB materials under the action of electric fields are solved, and efficient electrical insulation and optical performance improvements are achieved.
Patent Information
- Application Number
- CN202411665042.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-20
- Publication Date
- 2025-02-28
AI Technical Summary
PVB materials are prone to potential-induced attenuation (PID) effects under the action of electric fields, resulting in a degradation in the performance of photovoltaic modules and insufficient light transmittance, which affects the power generation efficiency of photovoltaic modules.
By combining the vapor phase silica nanoparticles with the PVB molecular chain through chemical grafting reaction, and introducing nanomaterials such as nano zinc oxide and nano cerium oxide, PVB-silica graft copolymers are formed, improving their electrical insulation properties, mechanical strength and transparency.
It significantly improves the PID resistance and light transmittance of the PVB intermediate film, extends the service life of photovoltaic modules, and improves the power generation efficiency.
Smart Images

Figure BDA0005144389350000161 
Figure BDA0005144389350000191 
Figure BDA0005144389350000192
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of polymer material synthesis, and specifically relates to a polyvinyl butyral intermediate film and a synthesis method and application thereof, and more specifically relates to a polyvinyl butyral intermediate film that is resistant to potential induced attenuation and has high transparency and a synthesis method and application thereof. Background Art
[0002] Polyvinyl butyral (PVB) is a high-performance polymer material that is widely used as a packaging material in photovoltaic modules. With the rapid development of the photovoltaic industry, building-integrated photovoltaics (BIPV) has gradually become an important application field. BIPV uses photovoltaic modules as part of building materials, which can not only generate electricity, but also replace traditional building materials for curtain walls, roofs, skylights, etc.
[0003] PVB resin plays the following main roles in BIPV modules: ① Encapsulation material: PVB resin is an encapsulation material for photovoltaic modules, mainly used for bonding and protection between laminated glass and solar cells. PVB provides good mechanical strength and weather resistance to ensure the stability and reliability of the modules in long-term use; ② Protective layer: PVB resin can effectively block the entry of water vapor and pollutants, protect the internal solar cells and other materials, and extend the service life of photovoltaic modules; ③ Insulation layer: Due to its good insulation properties, PVB resin can effectively prevent current leakage in BIPV modules to ensure the safe operation of the photovoltaic system.
[0004] In photovoltaic systems, the causes of the PID effect are as follows: ① Electric field effect: During the operation of photovoltaic modules, the modules will be exposed to the electric field for a long time, especially in high voltage and high humidity environments. The electric field will cause the charge in the module to move and accumulate, which will affect the electrical performance of the module; ② Ion migration: Under the action of the electric field, the ions in the module (such as sodium ions) will migrate, causing electrochemical reactions inside the module. These reactions will destroy the structure of the module and the electrical properties of the material. Surface leakage current: In a high humidity environment, a layer of conductive water film will form on the surface of the module, resulting in an increase in surface leakage current, which will also aggravate the PID effect.
[0005] Impact of PID effect: PID effect can cause the output power of photovoltaic modules to decrease, the conversion efficiency to decrease, and even cause module failure. The specific manifestations are: ① Reduced output power: Due to the accumulation and migration of charges, the internal resistance of the module increases, resulting in a decrease in output power; ② Reduced efficiency: The PID effect destroys the electrical properties of the module and reduces the photoelectric conversion efficiency; ③ Material degradation: Electrochemical reactions cause the degradation of module materials (such as packaging materials, EVA, etc.), affecting their long-term performance.
[0006] PVB materials are prone to potential induced degradation (PID) effect under the action of electric field, resulting in degradation of photovoltaic module performance. PID effect mainly occurs under high voltage and high humidity conditions, resulting in current leakage and module power degradation. The main reasons for the degradation of PVB resin's anti-PID performance are as follows:
[0007] High impurity content: During the synthesis of PVB resin, if the reaction is incomplete or the washing is not thorough, impurities will remain. These impurities will move under the action of the electric field, causing leakage inside the component, thereby exacerbating the PID effect.
[0008] Humidity and environmental conditions: PVB resin will absorb moisture in high humidity and high temperature environments, reducing its insulation performance. Water molecules will form conductive channels under the action of the electric field, aggravating current leakage and causing the PID effect.
[0009] Purity of PVB resin: Unreacted components or impure substances in PVB resin will undergo electrochemical reactions under the action of the electric field, destroying the structure of the resin and reducing its insulation properties and anti-PID capabilities.
[0010] Structural defects: During the production process, if the particle size distribution of the PVB resin powder is uneven or there are gaps, it will cause an electric field concentration effect, increase the local current density, and thus aggravate the PID effect.
[0011] High light transmittance is one of the important factors for improving the power generation efficiency of photovoltaic modules. However, the current PVB resin powder has the following pain points in terms of light transmittance:
[0012] Insufficient material purity: Residual impurities and unreacted products during the synthesis process will affect the transparency of PVB, resulting in a decrease in light transmittance.
[0013] Uneven particle size distribution: Uneven particle size distribution of PVB resin powder will cause light scattering, increase haze and reduce light transmittance.
[0014] Improper selection of additives: The use of inappropriate additives or fillers will introduce optical defects and affect the light transmission properties of the material.
[0015] Therefore, it is particularly important to develop a polyvinyl butyral interlayer film that has both anti-PID effect and high light transmittance. Summary of the invention
[0016] In view of the shortcomings of the prior art, the present invention aims to provide a polyvinyl butyral interlayer and its synthesis method and application, and more specifically to provide a polyvinyl butyral interlayer with high transmittance and resistance to potential induced attenuation and its synthesis method and application. The present invention designs the composition and synthesis method of the polyvinyl butyral interlayer, combines fumed silica nanoparticles with PVB molecular chains through a chemical grafting reaction, and simultaneously introduces nano zinc oxide (ZnO) and nano cerium oxide (CeO 2 ) and other nanomaterials to obtain PVB-silica graft copolymer to improve the electrical insulation properties, mechanical strength and transparency of polyvinyl butyral interlayer.
[0017] To achieve this object, the present invention adopts the following technical solutions:
[0018] In a first aspect, the present invention provides a method for synthesizing a polyvinyl butyral intermediate film, the method comprising the following steps:
[0019] (a) polyvinyl alcohol and butyraldehyde undergo acetal reaction to obtain PVB resin;
[0020] (b) using a silane coupling agent to perform surface modification on the fumed silica to obtain surface-modified fumed silica;
[0021] (c) Under alkaline conditions, the surface-modified fumed silica and polyvinyl alcohol undergo a grafting reaction to obtain a PVA-silica graft;
[0022] (d) in the presence of an acidic catalyst, the PVA-silica grafted product reacts with butyraldehyde for acetalization, and then the nanomaterial is added thereto for mixing, and then the mixture is washed with water, filtered, and dried to obtain a silica-grafted PVB-nanomaterial mixture;
[0023] The nanomaterials include nano zinc oxide and nano cerium oxide;
[0024] (e) mixing the silica-grafted PVB-nanomaterial mixture obtained in step (d) and the PVB resin obtained in step (a), and forming a film to obtain the polyvinyl butyral intermediate film.
[0025] The present invention designs the composition and synthesis method of polyvinyl butyral interlayer (PVB interlayer), combines fumed silica nanoparticles with PVB molecular chains through a chemical grafting reaction, and simultaneously introduces nano zinc oxide (ZnO) and nano cerium oxide (CeO 2) and other nanomaterials to obtain a silica-grafted PVB-nanomaterial mixture to improve the electrical insulation performance, mechanical strength and transparency of the polyvinyl butyral interlayer, thereby meeting the application requirements of BIPV photovoltaic modules. These modification measures can not only improve the anti-PID performance of the PVB interlayer and extend the service life of the photovoltaic module, but also improve its light transmittance and enhance the power generation efficiency.
[0026] In the present invention, PVA represents polyvinyl alcohol, and PVB represents polyvinyl butyral.
[0027] The following are preferred technical solutions of the present invention, but are not intended to limit the technical solutions provided by the present invention. Through the following preferred technical solutions, the objectives and beneficial effects of the present invention can be better achieved and realized.
[0028] As a preferred technical solution of the present invention, the purity of the polyvinyl alcohol and butyraldehyde is independently ≥99.9%, for example, it can be 99.9%, 99.91%, 99.92%, 99.93%, 99.94%, 99.95% or 99.96%, etc.
[0029] Preferably, the number average molecular weight of the polyvinyl alcohol is 70,000 to 100,000, for example, 70,000, 72,000, 75,000, 78,000, 80,000, 81,000, 84,000, 86,000, 88,000, 90,000, 93,000, 96,000, 98,000 or 100,000.
[0030] Preferably, in step (a), the mass ratio of the polyvinyl alcohol to the butyraldehyde is 1:(1.6-1.8), for example, it can be 1:1.6, 1:1.62, 1:1.64, 1:1.66, 1:1.68, 1:1.7, 1:1.72, 1:1.74, 1:1.76, 1:1.78 or 1:1.8, etc.
[0031] In the present invention, the comprehensive performance of the polyvinyl butyral intermediate film can be further optimized by controlling the mass ratio of the polyvinyl alcohol and the butyraldehyde in step (a) within a specific range, and the mass ratio of the butyraldehyde in step (d) and the polyvinyl alcohol in step (c) within a specific range.
[0032] Preferably, the temperature of the acetalization reaction in step (a) is 50-80°C (for example, it can be 50°C, 52°C, 55°C, 57°C, 60°C, 63°C, 66°C, 68°C, 70°C, 72°C, 75°C, 77°C or 80°C, etc.), and the time is 1-8h (for example, it can be 1h, 2h, 3h, 4h, 5h, 6h, 7h or 8h, etc.).
[0033] Preferably, the acetalization reaction in step (a) is carried out in the presence of a catalyst.
[0034] Preferably, the catalyst comprises an acidic catalyst, and the acidic catalyst comprises hydrochloric acid.
[0035] Preferably, the mass ratio of the hydrochloric acid to the polyvinyl alcohol in step (a) is (0.5-1):1, for example, it can be 0.5:1, 0.55:1, 0.6:1, 0.65:1, 0.7:1, 0.75:1, 0.8:1, 0.85:1, 0.9:1, 0.95:1 or 1:1, etc.
[0036] It should be noted that the present invention does not have any special restrictions on the mass concentration of hydrochloric acid, and hydrochloric acid solutions of commonly used mass concentrations in the art are applicable, including but not limited to: 20-35wt%, for example, 20wt%, 22wt%, 24wt%, 26wt%, 28wt%, 30wt%, 32wt%, 33wt% or 35wt%, etc.
[0037] As a preferred technical solution of the present invention, the D 50 The particle size is 10-20 nm (for example, it can be 10 nm, 11 nm, 12 nm, 13 nm, 14 nm, 15 nm, 16 nm, 17 nm, 18 nm, 19 nm or 20 nm, etc.), and the specific surface area is 200-300 m 2 / g (for example, it can be 200m 2 / g, 210m 2 / g, 220m 2 / g, 230m 2 / g, 240m 2 / g, 250m 2 / g, 260m 2 / g, 270m 2 / g, 280m 2 / g, 290m 2 / g or 300m 2 / g, etc.).
[0038] In the present invention, the fumed silica can be selected from commercial products that meet the above-mentioned properties, and the purity of the fumed silica is controlled to be ≥99.8%, for example, it can be 99.8%, 99.82%, 99.84%, 99.86%, 99.88%, 99.9%, 99.92%, 99.94% or 99.96%, etc.
[0039] Preferably, the silane coupling agent includes γ-glycidyloxypropyltrimethoxysilane (KH-560).
[0040] Preferably, the mass ratio of the fumed silica to the silane coupling agent is 1:(0.8-1.2), for example, it can be 1:0.8, 1:0.85, 1:0.9, 1:0.95, 1:1, 1:1.05, 1:1.1, 1:1.15 or 1:2, etc.
[0041] As a preferred technical solution of the present invention, the temperature of the surface modification in step (b) is 20-30°C (for example, it can be 20°C, 21°C, 22°C, 23°C, 24°C, 25°C, 26°C, 27°C, 28°C, 29°C or 30°C, etc.), and the time is 1-4h (for example, it can be 1h, 1.5h, 2h, 2.5h, 3h, 3.5h or 4h, etc.).
[0042] Preferably, the surface modification in step (b) is carried out in the presence of solvent A, and the solvent A comprises ethanol.
[0043] Preferably, the ratio between the mass of the fumed silica and the volume of solvent A is 1g:(35mL-45mL), for example, it can be 1g:35mL, 1g:36mL, 1g:37mL, 1g:38mL, 1g:39mL, 1g:40mL, 1g:41mL, 1g:42mL, 1g:43mL, 1g:44mL or 1g:45mL, etc.
[0044] Preferably, step (b) further comprises a post-treatment step after the surface modification, and the post-treatment method comprises filtering, washing and drying.
[0045] Preferably, step (b) specifically comprises the following steps:
[0046] mixing fumed silica and ethanol to form a suspension;
[0047] A silane coupling agent is added thereto, and surface modification is performed at 20-30° C. for 1-4 hours, followed by filtering, washing and drying to obtain the surface-modified fumed silica.
[0048] As a preferred technical solution of the present invention, the base forming the alkaline conditions in step (c) includes NaOH.
[0049] Preferably, the pH of the alkaline condition in step (c) is 9-10, for example, it can be 9, 9.1, 9.2, 9.3, 9.4, 9.5, 9.6, 9.7, 9.8, 9.9 or 10, etc.
[0050] Preferably, in step (c), the mass ratio of the surface modified fumed silica to polyvinyl alcohol is 1:(25-45), for example, it can be 1:25, 1:27, 1:30, 1:33, 1:36, 1:38, 1:40, 1:42, 1:43 or 1:45, etc.
[0051] The invention can further improve the electrical insulation performance, mechanical strength and transparency of the PVB intermediate film by controlling the mass ratio of the surface-modified fumed silica and polyvinyl alcohol within a specific range.
[0052] As a preferred technical solution of the present invention, the temperature of the grafting reaction in step (c) is 30-40°C (for example, it can be 30°C, 31°C, 32°C, 33°C, 34°C, 35°C, 36°C, 37°C, 38°C, 39°C or 40°C, etc.), and the time is 1.5-3h (for example, it can be 1.5h, 2h, 2.5h or 3h, etc.).
[0053] Preferably, the grafting reaction in step (c) is carried out in the presence of solvent B, and the solvent B comprises water.
[0054] Preferably, the grafting reaction in step (c) further includes a post-treatment step, wherein the post-treatment method includes adjusting the pH of the reaction system to neutral (pH 6.5-7.5, for example, 6.5, 6.6, 6.7, 6.8, 6.9, 7.0, 7.1, 7.2, 7.3, 7.4 or 7.5, etc.).
[0055] Preferably, the grafting reaction in step (c) specifically includes the following steps: mixing polyvinyl alcohol and solvent B to obtain a polyvinyl alcohol aqueous solution with a mass concentration of 10-15% (for example, it can be 10%, 11%, 12%, 13%, 14% or 15%, etc.), adding surface-modified fumed silica and NaOH thereto, carrying out the grafting reaction at a pH of 9-10 and 30-40°C for 1.5-3h, and then adjusting the pH of the reaction system to neutral.
[0056] As a preferred technical solution of the present invention, the acidic catalyst includes hydrochloric acid.
[0057] Preferably, the mass ratio of the hydrochloric acid to the polyvinyl alcohol in step (c) is (0.5-1):1, for example, it can be 0.5:1, 0.55:1, 0.6:1, 0.65:1, 0.7:1, 0.75:1, 0.8:1, 0.85:1, 0.9:1, 0.95:1 or 1:1, etc.
[0058] It should be noted that the present invention does not have any special restrictions on the mass concentration of hydrochloric acid, and hydrochloric acid solutions of commonly used mass concentrations in the art are applicable, including but not limited to: 20-35wt%, for example, 20wt%, 22wt%, 24wt%, 26wt%, 28wt%, 30wt%, 32wt%, 33wt% or 35wt%, etc.
[0059] Preferably, the mass ratio of butyraldehyde in step (d) to polyvinyl alcohol in step (c) is 1:(1.6-1.8), for example, it can be 1:1.6, 1:1.62, 1:1.64, 1:1.66, 1:1.68, 1:1.7, 1:1.72, 1:1.74, 1:1.76, 1:1.78 or 1:1.8, etc.
[0060] Preferably, the acetalization reaction in step (d) is carried out at a temperature of 50-80°C (for example, 50°C, 52°C, 55°C, 57°C, 60°C, 63°C, 66°C, 68°C, 70°C, 72°C, 75°C, 77°C or 80°C, etc.), and the reaction time is 1-8h (for example, 1h, 2h, 3h, 4h, 5h, 6h, 7h or 8h, etc.).
[0061] In the present invention, an appropriate amount of ethanol may be added as a solvent during the acetalization reaction in step (d) to enhance the solubility and uniformity of the reactants.
[0062] As a preferred technical solution of the present invention, the mass ratio of the nanomaterial to the polyvinyl alcohol in step (c) is 1:(20-45), for example, it can be 1:20, 1:22, 1:25, 1:27, 1:30, 1:33, 1:36, 1:38, 1:40, 1:41, 1:43 or 1:45, etc.
[0063] Preferably, the D of the nano zinc oxide 50 The particle size is 20-50nm (for example, it can be 20nm, 22nm, 25nm, 27nm, 30nm, 33nm, 36nm, 38nm, 40nm, 42nm, 44nm, 46nm, 49nm or 50nm, etc.), and the specific surface area is 50-100m 2 / g (for example, it can be 50m 2 / g, 55m 2 / g, 60m 2 / g, 65m 2 / g, 70m 2 / g, 75m 2 / g, 80m 2 / g, 85m 2 / g, 90m 2 / g, 95m 2 / g or 100m 2 / g, etc.).
[0064] In the present invention, commercially available nano zinc oxide with a purity of ≥99.5% (for example, 99.5%, 99.52%, 99.55%, 99.57%, 99.6%, 99.63%, 99.66%, 99.68%, 99.7% or 99.75%, etc.) can be selected.
[0065] Preferably, the D of the nano cerium oxide 50 The particle size is 30-60nm (for example, 30nm, 33nm, 36nm, 38nm, 40nm, 42nm, 44nm, 46nm, 49nm, 49nm, 52nm, 55nm, 57nm, 58nm or 60nm, etc.), and the specific surface area is 40-80m 2 / g (for example, it can be 40m 2 / g, 45m 2 / g, 50m 2 / g, 55m 2 / g, 60m 2 / g, 65m 2 / g, 70m 2 / g, 75m 2 / g or 80m 2 / g, etc.).
[0066] In the present invention, commercially available nano-cerium oxide with a purity of ≥99.5% (for example, 99.5%, 99.52%, 99.55%, 99.57%, 99.6%, 99.63%, 99.66%, 99.68%, 99.7% or 99.75%, etc.) can be selected.
[0067] Preferably, the mass ratio of the nano zinc oxide to the nano cerium oxide is (1-1.5):1, for example, it can be 1:1, 1.05:1, 1.1:1, 1.15:1, 1.2:1, 1.25:1, 1.3:1, 1.35:1, 1.4:1, 1.45:1 or 1.5:1, etc.
[0068] As a preferred technical solution of the present invention, the mixing method in step (d) includes physical mixing or chemical grafting.
[0069] Preferably, the mixing method in step (d) comprises the following steps:
[0070] The nanometer material is added into the reaction system after the acetal reaction, and the nanometer material is evenly dispersed in the PVB-silicon dioxide graft copolymer through high shear stirring or ultrasonic dispersion.
[0071] Preferably, the number of times of washing with water in step (d) is 15-20 times, for example, 15 times, 16 times, 17 times, 18 times, 19 times or 20 times.
[0072] The present invention can further improve the purity of the silicon dioxide grafted PVB-nano material mixture by controlling the number of water washings within a specific range, thereby improving the electrical insulation performance, mechanical strength and transparency of the PVB interlayer.
[0073] Preferably, in the water washing process of step (d), pure water with a conductivity of less than 10 μS / cm is used for final washing.
[0074] Preferably, the drying temperature in step (d) is 60-70°C, for example, it can be 60°C, 61°C, 62°C, 63°C, 64°C, 65°C, 66°C, 67°C, 68°C, 69°C or 70°C, etc.
[0075] Preferably, after drying in step (d), the moisture content of the silica grafted PVB-nanomaterial mixture is ≤0.5%, for example, it can be 0.2%, 0.24%, 0.26%, 0.28%, 0.3%, 0.33%, 0.36%, 0.39%, 0.42%, 0.45%, 0.48% or 0.5%, etc.
[0076] Preferably, the drying step further includes a post-processing step, and the post-processing method includes: crushing.
[0077] Preferably, the drying and pulverizing steps include:
[0078] The washed silica-grafted PVB-nanomaterial mixture is placed in an environment of 60-70° C. for drying until the moisture content is ≤0.5%;
[0079] The dried silica-grafted PVB-nano material mixture is crushed using a grinder to obtain a silica-grafted PVB-nano material mixture with uniform particle size.
[0080] As a preferred technical solution of the present invention, in step (e), the mass percentage of the silica grafted PVB-nanomaterial mixture is 4-6%, for example, 4%, 4.2%, 4.4%, 4.6%, 4.8%, 5%, 5.2%, 5.4%, 5.6%, 5.8% or 6%, etc., taking the sum of the mass percentages of the PVB resin in step (a) and the silica grafted PVB-nanomaterial mixture in step (d) as 100%.
[0081] Preferably, the film-making method in step (e) comprises an extrusion or casting process.
[0082] Preferably, the components for preparing the polyvinyl butyral intermediate film further include any one of an antioxidant, a plasticizer or a stabilizer, or a combination of at least two thereof.
[0083] It should be noted that in the present invention, there is no specific restriction on the specific selection and dosage of antioxidants, plasticizers and stabilizers, and the antioxidants, plasticizers and stabilizers commonly used in the art and their dosages are applicable. If the components of the polyvinyl butyral intermediate film also include antioxidants, plasticizers or stabilizers, the method for preparing the polyvinyl butyral intermediate film is: mixing a silica-grafted PVB-nanomaterial mixture, a polyvinyl butyral resin, an optional antioxidant, a plasticizer and a stabilizer, and preparing a film to obtain a polyvinyl butyral intermediate film.
[0084] In a second aspect, the present invention provides a polyvinyl butyral intermediate film prepared by the synthesis method described in the first aspect.
[0085] Preferably, the volume resistivity of the polyvinyl butyral intermediate film is ≥1×10 17 Ω·cm, for example, can be 1×10 17 Ω·cm、1.05×10 17 Ω·cm、1.1×10 17 Ω·cm、1.15×10 17 Ω·cm、1.2×10 17 Ω·cm、1.25×10 17 Ω·cm、1.3×10 17 Ω·cm、1.35×10 17 Ω·cm、1.4×10 17 Ω·cm、1.45×10 17 Ω·cm、1.5×10 17 Ω·cm、1.6×10 17 Ω·cm、1.8×10 17 Ω·cm or 2×10 17 Ω·cm, etc.
[0086] Preferably, the light transmittance of the polyvinyl butyral intermediate film is ≥90%, for example, it may be 90%, 91%, 92%, 93%, 94%, 95%, 96%, 97% or 98%.
[0087] Preferably, the haze of the polyvinyl butyral intermediate film is ≤0.5%, for example, it may be 0.5%, 0.4%, 0.3%, 0.2% or 0.1%.
[0088] The third aspect specifies that the present invention provides an application of the polyvinyl butyral intermediate film as described in the second aspect, wherein the polyvinyl butyral intermediate film is used to prepare a packaging material for a photovoltaic module.
[0089] Preferably, the polyvinyl butyral intermediate film is used for encapsulation of building-integrated photovoltaic modules.
[0090] The method for preparing the polyvinyl butyral intermediate film provided by the present invention specifically comprises the following steps:
[0091] 1. Raw material selection and surface treatment
[0092] High-purity polyvinyl alcohol (PVA) and butyraldehyde are selected as the main reactants. In order to ensure the high purity and low impurities of the final PVB resin, the purity of PVA and butyraldehyde is required to be above 99.9%. The mass ratio of PVA to butyraldehyde is (1.6-1.8):1 to ensure the full progress of the synthesis reaction and the stability of the final product.
[0093] Surface modification of fumed silica: In order to effectively graft fumed silica onto the PVB molecular chain, it needs to be surface modified. Select a silane coupling agent (such as γ-glycidyloxypropyltrimethoxysilane, KH-560) to treat the fumed silica so that its surface has active epoxy groups. The specific steps are as follows:
[0094] Disperse the fumed silica in ethanol to form a uniform suspension, then add the silane coupling agent KH-560 thereto, stir and react at 20-30°C for 1-4 hours to allow the silane coupling agent KH-560 to react with the surface of the fumed silica, filter, wash and dry the modified silica to ensure that its surface has uniform epoxy groups.
[0095] Surface modification reaction equation: SiO 2 +KH-560→SiO 2 -KH-560.
[0096] Nanomaterial characteristic parameters:
[0097] Fumed silica (SiO 2 ): Particle size 10-20nm, specific surface area 200-300m 2 / g, purity ≥99.8%.
[0098] Nano zinc oxide (ZnO): particle size 20-50nm, specific surface area 50-100m 2 / g, purity ≥99.5%.
[0099] Nano-cerium oxide (CeO 2 ): Particle size 30-60nm, specific surface area 40-80m 2 / g, purity ≥99.5%.
[0100] 2. Grafting reaction
[0101] PVA dissolution and reaction: PVA is dissolved in deionized water to prepare a 10-15% PVA aqueous solution. Stirring is maintained during the dissolution process and the dissolution temperature is controlled at 80-90°C to ensure that the PVA is completely dissolved.
[0102] Silica grafting: Add surface-modified silica to PVA aqueous solution and carry out grafting reaction at pH 9-10 (such as adding a small amount of NaOH to make the reaction system 9-10). The epoxy group opens the ring under alkaline conditions and reacts with the hydroxyl group on the PVA molecular chain to form a covalently bonded PVA-silica graft. The reaction process is as follows:
[0103] Slowly add the modified silica to the PVA aqueous solution, keep stirring evenly, add an appropriate amount of NaOH solution, adjust the pH value of the system to alkaline, and stir the reaction at 30-40°C for 2-3 hours to allow the epoxy group to fully open and react with the hydroxyl group on the PVA. After the reaction is completed, adjust the solution to neutral to obtain a PVA-silica graft.
[0104] Grafting mechanism:
[0105] The epoxy group of KH-560 opens under alkaline conditions and reacts with the hydroxyl group on PVA to form a covalent bond.
[0106] The grafted silica is stably connected to the PVA chain through covalent bonds, which increases the stability and uniformity of the system.
[0107] Grafting reaction equation: PVA-OH+SiO 2 -KH-560→→PVA-O-SiO 2 .
[0108] 3. Acetal reaction
[0109] Synthesis of PVB-silica graft copolymer: Under the action of an acidic catalyst, PVA-silica grafted material reacts with butyraldehyde to form PVB-silica graft copolymer. In order to ensure the uniformity and sufficiency of the reaction, ethanol or isopropanol can be added as a solvent. The specific steps are as follows:
[0110] Slowly add butyraldehyde to the neutral PVA-silica graft reaction system obtained in the above step, keep stirring evenly, add an acidic catalyst (such as hydrochloric acid), the reaction temperature is 30-40°C, the reaction time is 2-3 hours, and the butyraldehyde is fully reacted with the hydroxyl groups on the PVA to generate PVB chains. During the reaction, add an appropriate amount of ethanol or isopropanol to enhance the solubility and uniformity of the reactants and ensure the high transparency and low haze of the PVB interlayer.
[0111] 4. Add nanomaterials
[0112] The introduction of nano zinc oxide (ZnO) and nano cerium oxide (CeO 2 ): In order to further improve the electrical insulation performance and anti-PID effect of the PVB interlayer, the present invention introduces nano zinc oxide and nano cerium oxide. They are evenly dispersed in the PVB matrix by physical mixing or chemical grafting. The specific steps are as follows:
[0113] After the acetalization reaction is completed, nano zinc oxide and nano cerium oxide are added to the reaction system, and the nano materials are evenly dispersed in the PVB matrix through high shear stirring or ultrasonic dispersion technology to ensure the uniform distribution of the nano materials in the PVB matrix, so as to improve the overall performance of the silica grafted PVB-nano material mixture.
[0114] 5. Washing and filtering
[0115] Multiple washing and filtering: In order to remove reaction residues and catalysts and improve the purity of the silica grafted PVB-nanomaterial mixture, 15-20 washing and filtering are required. A small amount of surfactant (such as sodium dodecyl sulfate) can be added during the washing process to improve the washing effect.
[0116] The specific steps are as follows:
[0117] After the reaction is completed, add an appropriate amount of deionized water to the reaction system, stir evenly, use a filter for preliminary filtration to remove most of the impurities and unreacted substances, wash with water 15-20 times, filter after each wash to ensure purity, and add a small amount of surfactant during washing to further remove residual impurities. Use pure water with a conductivity of less than 10μS / cm for final washing to ensure the high purity of the silica-grafted PVB-nanomaterial mixture.
[0118] Water washing and filtration mechanism: Multiple water washings can reduce the impurity content by diluting and removing reaction residues. Surfactants can reduce interfacial tension during the washing process and improve the dissolution and removal efficiency of impurities. High-purity water washing further removes trace ions and residues, and improves the purity of the silica-grafted PVB-nanomaterial mixture.
[0119] 6. Drying and crushing
[0120] Drying and crushing: The washed silica grafted PVB-nanomaterial mixture needs to be dried and crushed to obtain a powder with uniform particle size. The specific steps are as follows:
[0121] The washed silica grafted PVB-nano material mixture is placed in an environment of 60-70°C for drying until the moisture content is less than 0.5%, and the dried silica grafted PVB-nano material mixture is crushed using a grinder to obtain silica grafted PVB-nano material mixture powder with uniform particle size. The temperature and speed during the crushing process are controlled to avoid excessive heat and mechanical stress, and to ensure the uniformity and stability of the powder.
[0122] 7. Preparation of PVB interlayer
[0123] Preparation of intermediate film: Add the silica grafted PVB-nano material mixture to the PVB resin at a ratio of 4-6wt%, and then mix it evenly with the optional antioxidant, stabilizer and plasticizer, and prepare the PVB intermediate film by extrusion or casting process. The specific steps are as follows:
[0124] Weigh 4-6wt% of silica grafted PVB-nano material mixture powder, add it to 94-96wt% of PVB resin, use a mixing device to mix evenly, ensure that the silica grafted PVB-nano material mixture and PVB resin are fully fused, and prepare the evenly mixed mixture into a polyvinyl butyral intermediate film through an extrusion or casting process to control the thickness and uniformity of the polyvinyl butyral intermediate film. Appropriate amounts of plasticizers, antioxidants and stabilizers can be added during the preparation process to improve the flexibility and stability of the intermediate film.
[0125] Through the above synthesis ideas, a silica-grafted PVB-nanomaterial mixture with high light transmittance and anti-PID effect can be effectively prepared, and it is added to PVB resin at a ratio of 4-6wt% to prepare a PVB interlayer with excellent performance. The film has high volume resistivity, low ash content, high light transmittance, low haze, good adhesion and mechanical properties, and has excellent anti-PID effect, radiation resistance, heat and humidity resistance, which significantly improves the performance and service life of photovoltaic modules.
[0126] Chemical reaction equations and mechanisms of surface modification and grafting reactions
[0127] Surface modification reaction mechanism: Initial state: Fumed silica (SiO 2 ) has a large number of hydroxyl groups (-OH) on the surface; coupling agent reaction: silane coupling agent (KH-560) reacts in ethanol solution through its methoxyl group (-OCH 3 ) and SiO 2 The hydroxyl groups on the surface undergo condensation reaction to form Si-O-Si covalent bonds and release methanol (CH 3OH); Epoxy group: The epoxy group of KH-560 molecule remains on the surface of silica, ready for further grafting reaction with the hydroxyl group on PVA.
[0128] Grafting reaction mechanism: Epoxy ring opening: At pH 9-10 (such as adding NaOH), the epoxy group of the KH-560 molecule undergoes a ring opening reaction to generate reactive hydroxyl groups (-OH) and ether bonds (-O-). Grafting reaction: The ring-opened epoxy group undergoes a nucleophilic addition reaction with the hydroxyl group (-OH) on the PVA chain to form a PVA-SiO 2 The covalent bond between (PVA-O-SiO 2 ).
[0129] Results: Silica nanoparticles were stably grafted onto the PVA molecular chains through silane coupling agents to form a uniformly distributed PVA-O-SiO 2 Graft.
[0130] 8. Grafting rate qualification line and characterization
[0131] In order to ensure that the performance of the PVB-silicon dioxide graft copolymer meets the expected requirements, the present invention needs to set a qualified line for the grafting rate and perform characterization tests after the material is synthesized.
[0132] According to the target application and performance requirements, the qualified line of grafting rate is set at more than 50%. This standard can ensure that a sufficient number of silica nanoparticles are successfully grafted onto the PVB molecular chain, thereby significantly improving the electrical insulation performance, mechanical strength and transparency of the material.
[0133] In order to confirm that the synthetic material reaches the set grafting rate qualification line, the following characterization test methods are required for analysis:
[0134] 1. Infrared spectroscopy (FTIR)
[0135] Test purpose: To detect the changes in the functional groups of the material before and after grafting and confirm the occurrence of the grafting reaction.
[0136] Test steps: Prepare the samples before and after grafting into thin films or powders. Use FTIR instrument to test the samples and obtain infrared spectra. Compare the infrared absorption peaks of the samples before and after grafting, especially the changes of PVA-OH and Si-O-Si bonds.
[0137] Analysis results: The Si-O-Si bond absorption peak (about 1100cm -1 ) and the absorption peak of PVA-OH (about 3300 cm -1 ) weakened, indicating the occurrence of grafting reaction. The change of grafting rate can be quantitatively analyzed by the change of absorbance ratio.
[0138] 2. Nuclear Magnetic Resonance (NMR)
[0139] Test purpose: To provide molecular structure information of grafted copolymers and calculate the grafting rate.
[0140] Test procedure: Dissolve the graft copolymer in an appropriate solvent to prepare the NMR sample. 1 H NMR and 13 The CNMR instrument tests the sample and obtains the NMR spectrum. The chemical shift and integral in the NMR spectrum are analyzed to determine the number and distribution of grafted molecules.
[0141] Analysis results: Pass 1 In the H NMR spectrum, CH 2 and CH 3 The peak of the group (about 1.2-2.0 ppm) and the peak of the silica grafted group (about 3.5-4.0 ppm) were integrated and compared to calculate the grafting rate.
[0142] Calculation formula: G = integral value 接枝基团 ÷(Integral value PVA基团 + Points Value 接枝基团 )×100%.
[0143] 3. Thermogravimetric analysis (TGA)
[0144] Test purpose: To determine the thermal stability and composition of the grafted copolymer and to confirm the efficiency of the grafting reaction.
[0145] Test steps: Prepare the samples before and after grafting to an appropriate mass and place them in the TGA instrument. Perform a temperature increase program and record the mass change of the samples at different temperatures. Analyze the TGA curve and compare the decomposition temperature and weight loss percentage of the samples before and after grafting.
[0146] Analysis results: The mass change of the grafted sample in the range of 200-400℃ is related to the decomposition of the grafted molecules. The mass of the grafted molecules can be calculated through the weight loss curve.
[0147] Calculation formula: G = ΔW 接枝 ÷W 总 ×100%;
[0148] ΔW 接枝 is the weight loss of the grafted sample in the range of 200-400°C;
[0149] W 总 is the total mass of the sample before grafting.
[0150] 4. Elemental analysis (EA)
[0151] Test purpose: To determine the content of elements in the grafted copolymer and calculate the grafting rate by the change of element content.
[0152] Test steps: Perform elemental analysis on the samples before and after grafting to determine the content of silicon, carbon, oxygen and other elements in the samples. Calculate the grafting rate by comparing the changes in the content of specific elements (such as silicon) in the samples before and after grafting.
[0153] Analysis results: The increase in silicon content in the grafted sample can be used to calculate SiO 2 The grafting rate.
[0154] Calculation formula: GEA = (C Si -C Si前 )÷C Si ×100%;
[0155] Where: C Si is the content of silicon in the sample after grafting.
[0156] C Si前 is the silicon content in the sample before grafting.
[0157] Through comprehensive analysis of the above-mentioned multiple characterization methods, it can be confirmed whether the grafting rate of the PVB-silicon dioxide graft copolymer reaches the qualified line (more than 50%), and the grafting reaction conditions can be further optimized to ensure that the material properties meet the application requirements. Taking the PVB-silicon dioxide graft copolymer provided in Example 1 of the present invention as an example, when characterizing its grafting rate, the specific data and calculation formula are as follows:
[0158] Infrared spectroscopy (FTIR) results
[0159] Before grafting: PVA-OH peak (3300cm -1 ) absorbance = 1.2, Si-O-Si peak (1100cm -1 ) absorbance = 0.3;
[0160] After grafting: PVA-OH peak absorbance = 0.8, Si-O-Si peak absorbance = 0.7;
[0161] Calculation formula: GFTIR = (A Si-O-Si,接枝后 -A Si-O-Si,接枝前 )÷A Si-O-Si,接枝前 ×100%;
[0162] Among them: A Si-O-Si is the absorbance of the Si-O-Si peak.
[0163] Calculation results: GFTIR = (0.7-0.3) ÷ 0.7 × 100% = 57.1%;
[0164] Nuclear Magnetic Resonance (NMR) Results
[0165] Before grafting: PVA group peak integral = 1.5
[0166] After grafting: PVA group peak integral = 1.2, grafted group peak integral = 0.8
[0167] Calculation formula: G = integral value 接枝基团 ÷(Integral value PVA基团 + Points Value 接枝基团 )×100%;
[0168] Calculation result: G = 0.8 ÷ (1.2 + 0.8) × 100% = 40%;
[0169] Thermogravimetric analysis (TGA) results
[0170] Before grafting: total mass = 10 mg
[0171] After grafting: weight loss in the range of 200-400℃ = 2mg
[0172] Calculation results: Elemental analysis (EA) results
[0173] Before grafting: Si content = 0.2%
[0174] After grafting: Si content = 0.6%
[0175] Calculation formula: G = ΔW 接枝 ÷W 总 ×100%;
[0176] Calculation result: G = (0.6-0.2) ÷ 0.6 × 100% = 66.7%;
[0177] Through the above characterization and calculation, it can be determined whether the grafting rate reaches the qualified line and ensure that the performance of the PVB-silica graft copolymer meets expectations.
[0178] 9. Performance Testing
[0179] Volume resistivity test: The volume resistivity of PVB-silica graft copolymer was tested using standard methods to ensure that it reached 1×10 15 Ohm cm or more.
[0180] Ash content test: The ash content of the copolymer was determined by the ignition method to ensure that it was less than 0.01%.
[0181] Light transmittance test: Test the light transmittance of the copolymer to ensure that its light transmittance is above 90%.
[0182] Haze test: The haze of the PVB interlayer is tested using a standard method to ensure that the haze is less than 0.5%.
[0183] Adhesion test: Test the adhesion of PVB interlayer between glass and solar cell to ensure that its bonding strength meets the application requirements.
[0184] Viscosity test: Test the viscosity of PVB resin to ensure its stability during processing.
[0185] Tensile strength test: Test the tensile strength of PVB interlayer to ensure that its mechanical properties meet application requirements.
[0186] Elongation at break test: Test the elongation at break of the PVB interlayer to ensure its toughness and durability.
[0187] Anti-PID effect test: Test the electrical properties of PVB interlayer under high humidity and high temperature conditions to ensure that it does not produce potential induced decay effect after long-term use.
[0188] Radiation resistance test: Test the stability of PVB interlayer under ultraviolet and other radiation conditions to ensure its radiation resistance.
[0189] Heat and humidity resistance test: Test the performance changes of PVB interlayer under high temperature and high humidity conditions to ensure its heat and humidity resistance.
[0190] Compared with the prior art, the present invention has the following beneficial effects:
[0191] The polyvinyl butyral (PVB) resin of the present invention has significant advantages in synthesis method and performance, and provides an excellent packaging material for photovoltaic modules, especially building integrated photovoltaics (BIPV). The following are five major advantages of the present invention:
[0192] (1) Excellent resistance to potential induced degradation (PID)
[0193] The PID effect is a common problem of photovoltaic modules under high voltage and high humidity conditions, which will lead to current leakage and module power attenuation. The present invention significantly improves the electrical insulation performance of PVB resin by grafting fumed silica nanoparticles onto PVB molecular chains. The grafted silica nanoparticles are evenly distributed in the PVB matrix to form a stable insulating network structure, which effectively prevents current leakage. Further introduction of nano zinc oxide (ZnO) and nano cerium oxide (CeO 2 ) and other nanomaterials, which have excellent electrical insulation and anti-oxidation properties, further enhancing the anti-PID effect of PVB resin. Through these modification measures, the electrical properties of PVB interlayer under high humidity and high temperature conditions are significantly improved, ensuring the stability and reliability of photovoltaic modules in long-term use.
[0194] (2) High light transmittance and low haze
[0195] Light transmittance is one of the important factors for improving the power generation efficiency of photovoltaic modules. The present invention ensures the high purity and low impurity content of PVB resin by optimizing the synthesis process. By using high-purity raw materials and multiple water washing steps, the impurities and unreacted products remaining in the synthesis process are removed, and the transparency of PVB resin is significantly improved. In addition, the uniform distribution of nanomaterials and the optimization of the grafting process reduce light scattering and haze, and improve the light transmittance of the PVB interlayer. Experiments have shown that the light transmittance of the PVB interlayer of the present invention is ≥90%, and the haze is ≤0.5%, which greatly improves the power generation efficiency of photovoltaic modules.
[0196] (3) Excellent mechanical properties
[0197] The PVB intermediate film not only plays a role in encapsulation and insulation in photovoltaic modules, but also needs to have good mechanical properties to withstand external stress and environmental changes. The present invention forms a nano-reinforced composite material by evenly distributing nano-silicon dioxide, zinc oxide and cerium oxide in the PVB matrix. The strong interaction between nanoparticles and PVB molecular chains significantly improves the mechanical strength and toughness of the material. Test results show that the PVB intermediate film of the present invention has excellent tensile strength and elongation at break, can effectively resist external mechanical stress, and ensure the long-term stability of photovoltaic modules in harsh environments.
[0198] (4) Excellent radiation resistance, heat resistance and humidity resistance
[0199] Photovoltaic modules are affected by environmental factors such as ultraviolet rays, temperature and humidity during use, resulting in material aging and performance degradation. The nano zinc oxide and nano cerium oxide introduced in the present invention not only improve the electrical insulation performance of the material, but also have excellent radiation resistance. Nano zinc oxide has good ultraviolet absorption capacity and can effectively block ultraviolet damage to PVB resin. Nano cerium oxide has excellent antioxidant properties and can prevent oxidative degradation of the material in high temperature and high humidity environments. Through these modification measures, the PVB intermediate film of the present invention performs well in radiation resistance, heat resistance and moisture resistance, significantly extending the service life of photovoltaic modules.
[0200] (5) Green and environmentally friendly preparation process
[0201] The present invention adopts a green and environmentally friendly preparation process in the synthesis process of PVB resin. By optimizing reaction conditions and process parameters, the use of harmful chemicals and the generation of waste are reduced. For example, silane coupling agents and alkaline solutions are used in surface modification and grafting reactions to avoid the use of strong acids, strong bases and toxic solvents. In addition, through multiple water washings and high-efficiency filtration, the high purity of the product is ensured and environmental pollution is reduced. The preparation process of the present invention not only complies with the principle of green chemistry, but also reduces production costs and has good prospects for industrial application.
[0202] In summary, the polyvinyl butyral (PVB) resin of the present invention has excellent anti-PID performance, high light transmittance and low haze, excellent mechanical properties, excellent radiation resistance and heat and moisture resistance, and green and environmentally friendly preparation process. These advantages make the application of the PVB resin of the present invention in photovoltaic modules, especially building integrated photovoltaic (BIPV) have significant competitiveness and broad market prospects. DETAILED DESCRIPTION
[0203] For the convenience of understanding the present invention, the present invention lists the following embodiments. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0204] The sources of some components in the embodiments and comparative examples are as follows:
[0205] Polyvinyl alcohol: polymer is 1700.
[0206] Example 1
[0207] The present embodiment provides a polyvinyl butyral interlayer and a preparation method thereof. The raw materials for preparing the polyvinyl butyral interlayer include the following components in parts by weight: PVB resin (95 parts), silica grafted PVB-nanomaterial mixture (5 parts) and antioxidant 1010 (1 part);
[0208] The preparation method of the polyvinyl butyral intermediate film comprises the following steps:
[0209] (a) Synthesis of PVB resin: Polyvinyl alcohol (170 g) and butyraldehyde (100 g) were mixed, hydrochloric acid (mass concentration of 30%, 115 g) was added thereto, and the mixture was reacted at 65° C. for 2.5 h to obtain PVB resin;
[0210] (b) Surface modification: 5 g of fumed silica was dispersed in 20 mL of ethanol, and a silane coupling agent KH-560 (5 g) was added. The mixture was stirred at room temperature for 2 h. After the reaction, the mixture was filtered, washed and dried to obtain the modified fumed silica.
[0211] (c) Grafting reaction: PVA (170 g) was dissolved in deionized water and stirred until completely dissolved to prepare a PVA aqueous solution with a mass concentration of 10%. The modified fumed silica (5 g) was slowly added to the PVA aqueous solution, and then a 0.05 mol / L NaOH solution was added to adjust the pH of the reaction system to 9. The grafting reaction was carried out at 35° C. for 2 hours. After the reaction was completed, the solution was adjusted to neutral (pH=7) to obtain a PVA-silica graft solution;
[0212] (d) Acetalization reaction: Butyraldehyde (100 g) and hydrochloric acid (mass concentration of 30%, 115 g) were slowly added to the PVA-silica graft solution, and the acetalization reaction was carried out at 65° C. for 2 hours. During the reaction, ethanol (50 mL) was added as a second solvent to enhance the solubility and uniformity of the reactants;
[0213] Adding nanomaterials: After the acetalization reaction is completed, add nano zinc oxide (3 g) and nano cerium oxide (3 g) to the above reaction system, and disperse the nanomaterials evenly in the PVB-silicon dioxide matrix by high shear stirring to obtain a crude silica-grafted PVB-nanomaterial mixture;
[0214] Washing and filtration: After the reaction is completed, the residual reactants and hydrochloric acid are removed by multiple washings. The number of washings is 20. After each washing, the filter is filtered and the final washing is performed using pure water with a conductivity of less than 10 μS / cm;
[0215] Drying and pulverizing: The washed silica grafted PVB-nanomaterial mixture is dried at 65°C to a moisture content of <0.5%, and the dried silica grafted PVB-nanomaterial mixture is pulverized using a grinder to obtain D 50 Silica grafted PVB-nanomaterial mixture with a particle size of 40nm.
[0216] (e) Preparation of PVB interlayer: The silica-grafted PVB-nanomaterial mixture obtained in step (d), the PVB resin obtained in step (a), and the antioxidant 1010 are mixed in proportion and then extruded to obtain a polyvinyl butyral interlayer (PVB interlayer) with a thickness of 1 mm.
[0217] Examples 2-4, Comparative Examples 1-4
[0218] Examples 2-4 and Comparative Examples 1-4 respectively provide a polyvinyl butyral intermediate film and a preparation method thereof, which differ from Example 1 only in that the raw material composition of the silica grafted PVB-nanomaterial mixture, the specific selection and dosage of the antioxidant are different, as shown in Table 1 below, and the other conditions are the same as Example 1.
[0219] Table 1
[0220]
[0221] The performance of the PVB interlayer provided in the above embodiments and comparative examples was characterized, and the specific test method was as follows:
[0222] 1. Volume resistivity detection
[0223] Volume resistivity is an important indicator to measure the insulation performance of materials. The method for detecting volume resistivity is as follows:
[0224] Sample preparation: Cut the PVB interlayer film sample into standard size (usually 10 cm×10 cm).
[0225] Environmental control: Place the sample in a constant temperature and humidity chamber with the temperature set to 23°C and the humidity set to 50% for more than 24 hours to ensure that the sample reaches the stable state required for the test.
[0226] Test instrument: Use a high-precision resistivity tester, and the test electrodes should cover the entire surface of the sample to ensure the accuracy of the test results.
[0227] Test process: Place the sample on the test platform of the resistivity tester, apply a certain voltage, and record the current value passing through the sample. Calculate the volume resistivity according to the formula: ρ = (V / I) × (A / d), where ρ is the volume resistivity, V is the voltage, I is the current, A is the electrode area, and d is the sample thickness.
[0228] 2. Ash content detection
[0229] Ash content indicates the content of inorganic matter in the material and is an important indicator for evaluating the purity of the material. The method for detecting ash content is as follows:
[0230] Sample preparation: Take a certain amount of PVB interlayer sample (about 5g) and record its initial mass m 0 .
[0231] Ashing treatment: Place the sample in a high-temperature muffle furnace, gradually raise the temperature to 600°C, and maintain it at this temperature for 2 hours to completely burn the organic matter in the sample and leave the inorganic matter.
[0232] Cooling and weighing: Cool the treated sample to room temperature and weigh its mass m 1 According to the formula: ash content (%) = (m 1 / m 0 )×100% to calculate the ash content.
[0233] 3. Light transmittance detection
[0234] Light transmittance is an important indicator to measure the transparency of materials. The higher the light transmittance, the better the transparency of the material. The method for testing light transmittance is as follows:
[0235] Sample preparation: Cut the PVB interlayer film sample into standard size (usually 10 cm×10 cm) and control the thickness to about 0.76 mm.
[0236] Environmental control: Place the sample in a constant temperature and humidity chamber with the temperature set to 23°C and the humidity set to 50% for more than 24 hours to ensure that the sample reaches the stable state required for the test.
[0237] Test instrument: Use a light transmittance tester, the light source wavelength is usually 550nm.
[0238] Test process: Place the sample on the test platform of the light transmittance tester and measure the luminous flux T passing through the sample. 1 and the luminous flux T without sample 0 According to the formula: Transmittance (%) = (T 1 / T 0 )×100% to calculate the transmittance.
[0239] 4. Haze detection
[0240] Haze is an important indicator to measure the light scattering ability of materials. The lower the haze, the better the transparency of the material. The method of detecting haze is as follows:
[0241] Sample preparation: Cut the PVB interlayer film sample into standard size (usually 10 cm×10 cm) and control the thickness to about 0.76 mm.
[0242] Environmental control: Place the sample in a constant temperature and humidity chamber with the temperature set to 23°C and the humidity set to 50% for more than 24 hours to ensure that the sample reaches the stable state required for the test.
[0243] Test instrument: Use a haze meter, the wavelength of the light source is usually 550nm.
[0244] Test process: Place the sample on the test platform of the haze meter, measure the total luminous flux T of the transmitted light and the diffuse luminous flux D of the transmitted light, and calculate the haze according to the formula: Haze (%) = (D / T) × 100%.
[0245] 5. Adhesion test
[0246] Adhesion is an important indicator to measure the adhesion between PVB interlayer and glass. The method of testing adhesion is as follows:
[0247] Sample preparation: The PVB interlayer was sandwiched between two sheets of glass and hot-pressed for 10 minutes at 100°C and 0.6 MPa using a hot press to prepare a composite sample.
[0248] Environmental control: Place the composite sample in a constant temperature and humidity chamber with the temperature set to 23°C and the humidity set to 50% for more than 24 hours to ensure that the sample reaches the stable state required for the test.
[0249] Test equipment: Use a tensile testing machine. The fixture should be able to hold the sample evenly to prevent the sample from sliding during the test.
[0250] Test process: Fix the sample on the tensile testing machine, apply uniform tensile force, record the maximum force value when the sample is detached, and calculate the bonding force according to the formula: bonding force (N / cm) = maximum force value / sample width.
[0251] 6. Viscosity detection
[0252] Viscosity is an important indicator to measure the flow properties of materials. The method for testing viscosity is as follows:
[0253] Sample preparation: PVB resin was dried and dissolved in ethanol to prepare a solution with a mass fraction of 10%.
[0254] Environmental Control: The sample solution was kept at 25°C in a constant temperature water bath to ensure the consistency of the test environment.
[0255] Test instrument: Use a rotational viscometer and select the appropriate rotor and speed to ensure the accuracy of the test results.
[0256] Test process: Pour the sample solution into the sample cup of the viscometer, start the viscometer, and record the viscosity value (mPa·s) after stabilization.
[0257] 7.Tensile strength and elongation at break test
[0258] Tensile strength and elongation at break are important indicators for measuring the mechanical properties of materials. The methods for testing tensile strength and elongation at break are as follows:
[0259] Sample preparation: Cut the PVB interlayer sample into a standard dumbbell-shaped specimen, the size of which complies with the provisions of GB / T 1040.1.
[0260] Environmental control: Place the sample in a constant temperature and humidity chamber with the temperature set to 23°C and the humidity set to 50% for more than 24 hours to ensure that the sample reaches the stable state required for the test.
[0261] Test equipment: Use a tensile testing machine. The fixture should be able to hold the sample evenly to prevent the sample from sliding during the test.
[0262] Test process: Fix the sample on a tensile testing machine, stretch the sample at a constant stretching speed (usually 50mm / min), and record the stress-strain curve of the sample during the stretching process. Calculate the tensile strength (MPa) and elongation at break (%) based on the curve.
[0263] 8. Anti-PID effect detection
[0264] The PID effect is a phenomenon in which photovoltaic modules experience power attenuation in high temperature and high humidity environments. The methods for detecting the anti-PID effect are as follows:
[0265] Sample preparation: The PVB interlayer was sandwiched between two sheets of glass and hot-pressed for 10 minutes at 100°C and 0.6 MPa using a hot press to prepare a composite sample.
[0266] Environmental control: The composite sample was placed in a constant temperature and humidity chamber with the temperature set at 85 °C and the humidity set at 85%, and a voltage of 1000 V was applied for 96 hours.
[0267] Test process: Measure the electrical properties (such as volume resistivity) of the sample before and after the test, and calculate the change rate of the electrical properties. The smaller the change rate, the better the anti-PID effect.
[0268] 9. Radiation resistance test
[0269] Radiation resistance is an indicator to measure the stability of material performance under long-term irradiation. The method for testing radiation resistance is as follows:
[0270] Sample preparation: Cut the PVB interlayer film sample into standard size (usually 10 cm×10 cm) and control the thickness to about 0.76 mm.
[0271] Environmental control: Place the sample in a constant temperature and humidity chamber with the temperature set to 23°C and the humidity set to 50% for more than 24 hours to ensure that the sample reaches the stable state required for the test.
[0272] Test equipment: Use ultraviolet irradiation test box, the light source wavelength is 340nm, and the irradiation intensity is 0.68W / m 2 .
[0273] Test process: Place the sample in a UV irradiation test box for 500 hours, measure the light transmittance of the sample before and after the test, and calculate the change rate of light transmittance. The light transmittance change rate is less than 0.5% and is considered qualified.
[0274] 10. Heat and humidity resistance test
[0275] Heat and humidity resistance is an indicator to measure the performance stability of materials in high temperature and high humidity environments. The methods for testing heat and humidity resistance are as follows:
[0276] Sample preparation: The PVB interlayer was sandwiched between two sheets of glass and hot-pressed for 10 minutes at 100°C and 0.6 MPa using a hot press to prepare a composite sample.
[0277] Environmental control: The composite samples were placed in a constant temperature and humidity chamber with the temperature set at 85 °C and the humidity set at 85% for 1000 hours.
[0278] Test process: Measure the appearance and performance changes of the sample before and after the test, especially observe the impact distance of the sample edge. The impact distance is less than 11mm, which is qualified.
[0279] The above performance test results are detailed in Table 2 and Table 3:
[0280] Table 2
[0281]
[0282] Table 3
[0283]
[0284]
[0285] Data analysis
[0286] From the performance test data of the above examples and comparative examples, it can be seen that the addition of modified fumed silica and nano zinc oxide and nano cerium oxide has a significant effect on the performance of the PVB interlayer. The following is a detailed analysis of the performance data:
[0287] 1. Volume resistivity:
[0288] The volume resistivity of Examples 1 to 4 is all within 1.1×10 17 Ω·cm, which is significantly higher than that of Comparative Examples 1 to 4 (volume resistivity ≤ 2.5×10 16 Ω·cm). This shows that after adding modified fumed silica and nanomaterials of specific composition, the insulation performance of PVB interlayer has been greatly improved, which helps to improve the material's electrical resistance and reduce current leakage.
[0289] 2.Ash content:
[0290] The ash content in the examples is below 0.005%, while the ash content in the comparative examples is above 0.015%. Low ash content indicates high material purity and few impurities, which helps to improve the transparency and mechanical properties of the material. The modified fumed silica and nanomaterials of specific composition used in the examples play a positive role in removing impurities.
[0291] 3. Light transmittance:
[0292] The light transmittance of the embodiments is generally above 90%, with the highest reaching 92% (Example 3), while the light transmittance of the comparative example is ≤89%. High light transmittance is crucial for photovoltaic modules, as it can effectively improve the photoelectric conversion efficiency. The addition of modified fumed silica and nanomaterials of specific composition improves the transparency of the PVB interlayer and optimizes the optical properties.
[0293] 4. Haze:
[0294] The haze of the embodiments is below 0.4%, with the lowest reaching 0.3% (Example 3), while the haze of the comparative examples is above 0.5%. Low haze means better transparency of the material and less light scattering, which helps to improve the efficiency of photovoltaic modules. The addition of modified fumed silica and nanomaterials of specific composition helps to reduce light scattering and improve the clarity of the film.
[0295] 5. Adhesion:
[0296] The bonding force of the examples is above 40 N / cm, with the highest reaching 43 N / cm (Example 3), while the bonding force of the comparative example is ≤ 40 N / cm. The higher bonding force helps to enhance the adhesion between the PVB interlayer and the glass, and increase the structural strength and durability of the photovoltaic module. The addition of modified fumed silica and specific composition nanomaterials improves the bonding performance of the film.
[0297] 6. Viscosity:
[0298] The viscosity of the examples is between 255 mPa·s and 265 mPa·s, which is slightly higher than that of the comparative examples. The moderately increased viscosity indicates that the fluidity of the material is slightly reduced, but this has little effect on the processing and helps to enhance the mechanical properties and stability of the film.
[0299] 7.Tensile strength and elongation at break:
[0300] The tensile strength and elongation at break of the examples are higher than those of the comparative examples, especially the tensile strength of Example 3 reaches 24 MPa and the elongation at break reaches 225%. Higher tensile strength and elongation at break indicate that the material has better mechanical properties and durability, which is crucial for the application of photovoltaic modules in various environments. The addition of modified fumed silica and nanomaterials of specific composition significantly enhances the mechanical properties of the PVB interlayer.
[0301] 8. Anti-PID effect:
[0302] The anti-PID effect of the embodiments is good, with a decay rate of less than 1%, while the decay rates of comparative examples 1 and 2 are ≥ 2%, and can even reach more than 10%. The addition of modified fumed silica and nanomaterials of specific composition effectively improves the anti-PID effect ability of the PVB interlayer and reduces the power decay of photovoltaic modules in high temperature and high humidity environments.
[0303] 9. Radiation resistance, heat resistance and humidity resistance:
[0304] The radiation resistance, heat resistance and humidity resistance of the embodiment are excellent, the transmittance change rate is within 0.5%, and the impact distance is within 11mm. The transmittance change rate and impact distance of the comparative example are significantly worse, at 1% and above 12mm, respectively. This shows that the addition of modified fumed silica and nanomaterials of specific composition significantly improves the stability and durability of the PVB interlayer, allowing it to maintain good performance under long-term irradiation and high temperature and high humidity environments.
[0305] In summary, the addition of modified fumed silica, nano zinc oxide and nano cerium oxide can significantly improve the performance of PVB interlayer, especially in improving electrical properties, optical properties, mechanical properties and environmental stability.
[0306] The present invention provides a synthesis method and application of a polyvinyl butyral interlayer (PVB interlayer) that is resistant to potential induced attenuation and has high transparency. By introducing fumed silica nanoparticles and nano zinc oxide (ZnO), nano cerium oxide (CeO 2 ) and other nanomaterials have achieved multiple modifications to PVB resin, significantly improving the electrical insulation properties, mechanical strength and transparency of the PVB interlayer, giving it significant advantages in use in photovoltaic modules, especially building integrated photovoltaic (BIPV) modules.
[0307] First, the present invention forms a PVB-silicon dioxide graft copolymer by grafting fumed silicon dioxide nanoparticles onto PVB molecular chains. This modification method not only improves the electrical insulation performance of PVB resin, but also enhances its mechanical strength. The grafted silicon dioxide nanoparticles are evenly distributed in the PVB matrix to form a stable insulating network structure, effectively preventing current leakage, thereby significantly improving the material's resistance to potential induced decay (PID) effect. In addition, the introduction of nano zinc oxide and nano cerium oxide further enhances the electrical insulation and antioxidant properties of PVB resin, significantly improving its electrical properties under high humidity and high temperature conditions, and ensuring the stability and reliability of photovoltaic modules in long-term use.
[0308] Secondly, the present invention ensures the high purity and low impurity content of the PVB resin and the silica-grafted PVB-nano material mixture by optimizing the synthesis process and material selection.
[0309] Through multiple water washing and high-efficiency filtration, the impurities and unreacted products remaining in the synthesis process are removed, and the transparency of the PVB interlayer is significantly improved. In addition, the uniform distribution of nanomaterials and the optimization of the grafting process reduce light scattering and haze, and improve the transmittance of the PVB interlayer. Experimental data show that the transmittance of the PVB interlayer of the present invention is above 90%, and the haze is less than 0.5%, which greatly improves the power generation efficiency of photovoltaic modules. In terms of mechanical properties, the PVB interlayer of the present invention performs well. The uniform distribution of nano-silicon dioxide, zinc oxide and cerium oxide forms a nano-reinforced composite material, which significantly improves the mechanical strength and toughness of the material. The test results show that the PVB interlayer of the present invention has excellent tensile strength and elongation at break, can effectively resist external mechanical stress, and ensure the long-term stability of photovoltaic modules in harsh environments.
[0310] In addition, the PVB interlayer of the present invention also exhibits excellent radiation resistance, heat resistance and humidity resistance. Nano zinc oxide has good ultraviolet absorption capacity, which can effectively prevent ultraviolet damage to the PVB interlayer. Nano cerium oxide has excellent antioxidant properties, which can prevent the material from oxidative degradation in high temperature and high humidity environments. Through these modification measures, the PVB interlayer of the present invention can still maintain good performance under long-term radiation and high temperature and high humidity environments, significantly extending the service life of photovoltaic modules.
[0311] In practical applications, the PVB interlayer of the present invention is not only suitable for conventional photovoltaic modules, but also for the packaging of building integrated photovoltaic (BIPV) modules. BIPV uses photovoltaic modules as part of building materials, which can not only generate electricity, but also replace traditional building materials for curtain walls, roofs, skylights, etc. Since the PVB interlayer of the present invention has high light transmittance and low haze, excellent mechanical properties and electrical insulation properties, it is particularly suitable for packaging materials of BIPV modules, which can significantly improve the performance and service life of photovoltaic modules.
[0312] In summary, the present invention significantly improves the electrical insulation performance, mechanical strength and transparency of the PVB interlayer through multiple modification methods such as grafting of fumed silica nanoparticles, introduction of nano zinc oxide and nano cerium oxide, and solves the problem that the PVB interlayer is prone to potential induced decay (PID) effect under the action of an electric field. At the same time, by optimizing the synthesis process and material selection, the high purity and low impurity content of the PVB resin and the silica-grafted PVB-nanomaterial mixture are ensured, and the light transmittance and mechanical properties of the PVB interlayer are improved. Finally, the PVB interlayer of the present invention shows excellent performance and broad market prospects in the application of photovoltaic modules, especially building integrated photovoltaic (BIPV) modules.
[0313] The applicant declares that the present invention illustrates the detailed process flow of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned detailed process flow, that is, it does not mean that the present invention must rely on the above-mentioned detailed process flow to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. A method for synthesizing a polyvinyl butyral resin / intermediate film, characterized in that: The synthesis method comprises the following steps: (a) polyvinyl alcohol and butyraldehyde undergo acetal reaction to obtain PVB resin; (b) using a silane coupling agent to perform surface modification on the fumed silica to obtain surface-modified fumed silica; (c) Under alkaline conditions, the surface-modified fumed silica and polyvinyl alcohol undergo a grafting reaction to obtain a PVA-silica graft; (d) in the presence of an acidic catalyst, the PVA-silica grafted product reacts with butyraldehyde for acetalization, and then the nanomaterial is added thereto for mixing, and then the mixture is washed with water, filtered, and dried to obtain a silica-grafted PVB-nanomaterial mixture; The nanomaterials include nano zinc oxide and nano cerium oxide; (e) mixing the silica-grafted PVB-nanomaterial mixture obtained in step (d) and the PVB resin obtained in step (a), and forming a film to obtain the polyvinyl butyral intermediate film.
2. The synthesis method according to claim 1, characterized in that The purity of the polyvinyl alcohol and butyraldehyde is independently ≥ 99.9%; In step (a), the mass ratio of the polyvinyl alcohol to the butyraldehyde is 1:(1.6-1.8).
3. The synthesis method according to claim 1, characterized in that The silane coupling agent includes γ-glycidyloxypropyltrimethoxysilane; The mass ratio of the fumed silica to the silane coupling agent is 1:(0.8-1.2).
4. The synthesis method according to claim 1, characterized in that In step (c), the mass ratio of the surface-modified fumed silica to polyvinyl alcohol is 1:(25-45).
5. The synthesis method according to claim 1, characterized in that The mass ratio of butyraldehyde in step (d) to polyvinyl alcohol in step (c) is 1:(1.6-1.8).
6. The synthesis method according to claim 1, characterized in that The mass ratio of the nano material to the polyvinyl alcohol in step (c) is 1:(20-45); The mass ratio of the nano zinc oxide to the nano cerium oxide is (1-1.5):
1.
7. The synthesis method according to claim 1, characterized in that The number of times of washing in step (d) is 15-20 times; In the water washing process of step (d), pure water with a conductivity of less than 10 μS / cm is used for final washing.
8. The synthesis method according to claim 1, characterized in that In step (e), the mass percentage of the silica-grafted PVB-nanomaterial mixture is 4-6%, taking the sum of the mass percentages of the PVB resin in step (a) and the silica-grafted PVB-nanomaterial mixture in step (d) as 100%.
9. A polyvinyl butyral intermediate film prepared by the synthesis method according to any one of claims 1 to 8.
10. An application of the polyvinyl butyral intermediate film as claimed in claim 9, characterized in that: The polyvinyl butyral intermediate film is used for preparing packaging materials for photovoltaic modules.
Citation Information
Cited By
Reinforced PVB (polyvinyl butyral) composite material added with nano silicon dioxide
CN121851586A